ASEAN Connectivity: Challenge for an Integrated ASEAN Community - Vineles, Phidel (2017)
It is crucial for the success of the ASEAN Community to strengthen and build its intra-regional connectivity. This will lead to more investments in business and industry towards a more inclusive region.